A Comprehensive Study on Software Development Lifecycle and Systematic Analysis of It Challenges (International Journal of Food and Nutritional Sciences, 2022)
The Software Development Lifecycle (SDLC) was used for the software industry to comprehend, execute, and create software products that are of the highest caliber, reliability, efficiency, and timeliness. It is sometimes referred to as a software development process model. There are many SDLC major approaches from which to choose. In this paper, the author tried to define a few SDLC concepts in terms of their most practical uses. The desktop seems to be a need in today's culture given how often it is utilized in industries like banking, education, entertainment, etc. eases the burden of providing software support. Many companies create software solutions with these qualities because programs must deal with complicated, protracted, and repeated activities in a short period of time. Governments, banks, and businesses, for instance, will also be able to fulfill contractual obligations more rapidly. The future potential of SDLC is it can be used in the home cycle of automation and in internet of things also.